Comparison of milk, sports drink and water in rehydrating rugby players - Alagappan, Patmavathy (2016)
This study was carried out to assess the effectiveness of milk (M), sodium added milk (Na+M), sports drink (SD) and water (W) for restoring fluid balance after exerciseinduced dehydration among 25 UPM rugby players. It also compared the after-effects of consuming all these drinks after exercise-induced dehydration. A randomized crossover counterbalanced designed was utilized to compare the after-effects of consuming the four previously mentioned fluids after running on a threadmill intermittently in a hot and humid environment to lose 1.7 + 0.1% of body mass (BM). Drinking commenced 20 min after the end of exercise and participants drank M, Na+M, SD, or W equivalent to 150% of their BM lost. Urine samples were collected to assess fluid balance. Participants were also asked to rate the after-effects experienced. Urine excretion over the recovery period did not change much during the M and Na+M trials whereas there was a marked increase in output between 1h and 2h after drinking water and sports drink. Cumulative urine output was significantly less (p = 0.0001) after the consumption of M (817.35 + 327.16 ml) and Na+M (642.78 + 316.30 ml) compared to W (1410.04 + 525.25 ml) and SD (1162.70 + 378.92 ml). Subjects remained in net positive fluid balance (euhydrated) throughout the recovery period after drinking M and Na+M but returned to net negative fluid balance 1h after drinking the other drinks; SD and W. However, participants experienced more stomach pain/discomfort and diarrhoea after M (48%) and Na+M (68%) consumption, while the consumption of SD and W did not seem to induce diarrhoea. The results suggest that sports drinks may be a more effective post-exercise rehydration drink for Asian athletes as the higher frequency of lactose intolerance after milk intake may affect the state of fluid balance. Sodium added milk can be considered for use after exercise by athletes accustomed to drinking milk or for those who are able to tolerate lactose intake.